Empirical and Numerical Analysis of Aerodynamic Drag on a Typical SUV Car Model at Different Locations of Vortex Generator - P. N. Selvaraju (Journal of Applied Fluid Mechanics, 2019)
The aerodynamic characteristics are concerned with the fuel consumption rate and the stability of a high speed vehicle. The current research aims at studying the aerodynamic behavior of a typical SUV vehicle model mounted with the vortex generator (VG) at various linear positions with reference to its rear roof edge. The flow field around the vehicle model was observed at different wind speed conditions. It had been determined that at the instance of lower wind speed, the VG had minimal effects of aerodynamic drag on the vehicle body. However, at the instance of higher wind speed conditions the magnitude of the drag force decreased significantly. Vehicles move at higher speeds in the highways, location of the VG varied towards the upstream of the vehicle due to early flow separation. Therefore test were conducted at different wind speeds and locations of VG. The numerical simulation conduced in this study provides flow characteristics around the vehicle model for different wind speeds. The realizable k−ε model was used to simulate and validate the empirical results in an effective manner. By using experimental data, the drag was reduced by 9.04 % at the optimized VG location. The results revealed that the induced aerodynamic drag would determine the best car shape. This paper provides a better understanding of VG positioning for enhanced flow separation control.